The Influence Of Profitability, Leverage And Company Size On Company Value With Asset Growth As A Moderator - Sinta Veronika Tumiwa; Abdul Kahar; Selmita Paranoan; Andi Ainil Mufidah Tanra (Jurnal Ilmiah Global Education, 2026)
This study examines the extent to which profitability, leverage, and firm size contribute to changes in firm value, while also evaluating the role of asset growth as a moderating variable in this relationship. Using a quantitative positivist approach, data analysis used moderated regression (MRA), where data sources were obtained through documentation of financial statements and annual reports of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. Purposive sampling was used to select the sample in this study based on several predetermined criteria, resulting in the selection of 11 companies as the research sample. The test results found that firm value was positively and significantly influenced by profitability and firm size, while leverage showed no significant effect. Asset growth did not moderate the relationship between profitability and firm value, but was shown to strengthen the effect of leverage and weaken the effect of firm size on firm value. Practically, this confirms that efforts to increase firm value can be directed through profitability optimization and better asset management, so that business expansion can run efficiently and increase investor confidence.